Transperineal prostate biopsy guided by which ultrasound transducer: transrectal or transperineal: a retrospective study - Yang Xiao; Lina Han; Han Wang; Guorong Lyu; Shilin Li (PeerJ)
Background Prostate biopsies are primarily conducted using either the transrectal or transperineal approach, with the ultrasound probe positioned in the rectum to obtain a clear view of the prostate. Reports on the utilization of transperineal prostate biopsies with the ultrasound probe placed on the perineal skin are limited. Methods A retrospective investigation was conducted on 119 patients who underwent transperineal ultrasound guided transperineal prostate biopsy (TP-TPPB). Additionally, 85 patients who underwent transrectal ultrasound guided transperineal prostate biopsy (TR-TPPB) were included as controls. The prostate cancer detection rates (PCDRs) and postoperative complication rates were compared between the two groups, and their application values were also evaluated. Results The overall PCDRs were 35.3% (42/119) in the TP-TPPB and 32.9% (28/85) in the TR-TPPB group (χ2 = 0.122, p = 0.727). When categorized by PSA level, there was no significant difference between the two groups in PCDRs in any category (p > 0.05). However, the single-needle PCDRs in some regions (L4, L5, R2, and apex) showed significant differences (p < 0.05). There was no difference in postoperative complication rates between the groups. Conclusion The PCDRs and the postoperative complication rates of TP-TPPB and TR-TPPB are similar. However, TP-TPPB requires simpler equipment and does not require intestinal preparation, which is especially useful for patients with rectal contraindications, such as those with severe hemorrhoids and rectal/anal diseases.